2009
DOI: 10.1123/jsr.18.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Knee Valgus, Hip-Muscle Strength, and Hip-Muscle Recruitment during a Single-Limb Step-Down

Abstract: Gluteus maximus recruitment might have greater association with reduced knee valgus in women than does external-rotation strength during step-down tasks. Gluteus medius strength might be associated with increased knee valgus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
140
5
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(155 citation statements)
references
References 26 publications
5
140
5
5
Order By: Relevance
“…29 Although the reasons underlying the biomechanical profile exhibited by females are not entirely clear, there is growing evidence to suggest that proximal factors may play a contributory role. As noted above, several studies have reported that reduced hip strength is related to greater knee valgus angles 17,30,32,81 and valgus moments. 35 Pollard et al 57 suggests that higher knee valgus angles and moments observed in female athletes is representative of a movement strategy in which there is insufficient utilization of the hip extensors to decelerate the body center of mass.…”
Section: Tibiofemoral Joint Injury Mechanisms: Proximal Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Although the reasons underlying the biomechanical profile exhibited by females are not entirely clear, there is growing evidence to suggest that proximal factors may play a contributory role. As noted above, several studies have reported that reduced hip strength is related to greater knee valgus angles 17,30,32,81 and valgus moments. 35 Pollard et al 57 suggests that higher knee valgus angles and moments observed in female athletes is representative of a movement strategy in which there is insufficient utilization of the hip extensors to decelerate the body center of mass.…”
Section: Tibiofemoral Joint Injury Mechanisms: Proximal Factorsmentioning
confidence: 99%
“…Because the foot is fixed to the ground, the inward movement of the knee joint causes the tibia to abduct and the foot to pronate, the end result being dynamic knee valgus (FIGURE 1). Excessive knee valgus has been shown to be related to diminished hip muscle strength 17,30,32,81 and has been implicated in contributing to numerous knee injuries, including anterior cruciate ligament (ACL) injury 29 and patellofemoral joint dysfunction. 58 It has been reported that hip adduction is the primary contributor to excessive dynamic knee valgus.…”
Section: Tibiofemoral Joint Proximal Contributions To Abnormal Tibiofmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PFPS is associated with decreased hip strength, specifically in the abductors and external rotators (1,2,(8)(9)(10)(11)(12)(13)(14)(15)(16). Since the hip abductors can affect knee valgus by controlling the frontal plane position of the femur, increasing hip abduction strength may help these patients (17).…”
Section: Introductionmentioning
confidence: 99%
“…The researcher stabilised the pelvis with one hand and applied medially directed resistance with the dynamometer in the other hand, just proximal to the greater trochanter of the femur. [16] contact, in order to measure club head speed and ball speed, and ball landing distance.…”
Section: Fig 1 Kinesio-taping Of the Gluteus Medius Musclementioning
confidence: 99%